1996
DOI: 10.1016/0005-2736(95)00205-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fusogenic and DNA-binding amphiphilic compounds on the receptor-mediated gene transfer into hepatic cells by asialofetuin-labeled liposomes

Abstract: Effects of fusogenic and DNA-binding amphiphilic compounds on the receptor-mediated gene transfer using asialofetuin-labeled liposomes (AF-liposomes) were examined with HepG2 cells and rat hepatocytes in primary culture. AF-liposomes were sufficiently taken up by both types of cells through the asialoglycoprotein receptor-mediated endocytosis. In HepG2 cells, bacterial beta-galactosidase (beta-Gal) gene expression was observed by transfection using AF-liposomes encapsulating plasmid pCMV beta DNA (AF-liposome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…AF, which is a glycoprotein having galactose residues, competes with galactose residues for the specific recognition by ASGP-R and thereby inhibits ASGP-R-mediated endocytosis. 17,18) The inhibition of the association by AF indicates the involvement of galactose-modified carriers such as liposomes modified with AF 19) or galactosylated lipid 20) with ASGP-R-mediated endocytosis. The association of SG-liposomes was significantly reduced by addition of 1 mg/ml AF (pϽ0.05), unlike non-SGliposomes.…”
Section: Effects Of Af On the Association Of Sg-liposomes Withmentioning
confidence: 99%
“…AF, which is a glycoprotein having galactose residues, competes with galactose residues for the specific recognition by ASGP-R and thereby inhibits ASGP-R-mediated endocytosis. 17,18) The inhibition of the association by AF indicates the involvement of galactose-modified carriers such as liposomes modified with AF 19) or galactosylated lipid 20) with ASGP-R-mediated endocytosis. The association of SG-liposomes was significantly reduced by addition of 1 mg/ml AF (pϽ0.05), unlike non-SGliposomes.…”
Section: Effects Of Af On the Association Of Sg-liposomes Withmentioning
confidence: 99%
“…Various liposomal formulations containing modified galactolipids have been optimized for maximum liver uptake. 26,27 Hara et al [28][29][30] reported that AF-labeled liposomes encapsulating plasmid DNA is effective in gene expression after intraportal injection with a preload of EDTA. On the other hand, Zanta et al 31 reported ASGPr-mediated in vitro gene delivery by a 5% galactose-bearing-PEIpolymer.…”
Section: Introductionmentioning
confidence: 99%
“…17) Overexpression of cyclin A contributes to the high proliferative activity of hepatoma, 18) indicating that the cyclin A promoter is active in such cells. Therefore we examined the gene expression in the hepatoma cell line HepG2 under the regulation of the cyclin A promoter using AF-liposomes, which can deliver genes specifically to hepatic cells through the AgpR, 11,12) as a nonviral vector. Polyplex Formation and Encapsulation into AF-Liposomes To encapsulate pCyclin A-Luc into AF-liposomes, DNA condensation was carried out by means of electrostatic interaction with PLL.…”
Section: Resultsmentioning
confidence: 99%
“…10) The formation of the DNA-PLL complex (polyplex) was evaluated in the gel retardation assay: samples (10 ml) were elec- 12) Briefly, palmitoyl-AF (125 mg as AF) dissolved in 50 ml of 10 mM Tris-HCl buffer (pH 7.5) containing 2% sodium deoxycholate (DOC) was added to 1 mmol of liposomal lipid film and mixed micelles were prepared by vigorous vortexing. DOC was dialyzed against 10 mM Tris-HCl buffer (pH 7.5) for 24 h, and empty AF-liposomes were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation